Little dogs rock! (New York : Bearport Pub., 2009)
Provides an introduction to various small breeds of dog, including beagles, dachshunds, and toy poodles, that discusses each breed's history, physical characteristics, and behaviors and looks at their roles in popular culture.
Beagle -- Chihuahua -- Dachshund -- Jack Russell Terrier -- Pomeranian -- Pug -- Toy Poodle -- Yorkshire Terrier.
Includes bibliographical references and indexes.
4.6
3-6
Keywords: Dogs -- Juvenile literature; Dogs; Dogs